The core proteome and pan proteome of Salmonella Paratyphi A epidemic strains. - Li Zhang; Di Xiao; Bo Pang; Qian Zhang; Haijian Zhou; Lijuan Zhang; Jianzhong Zhang; Biao Kan (PLoS ONE)
Comparative proteomics of the multiple strains within the same species can reveal the genetic variation and relationships among strains without the need to assess the genomic data. Similar to comparative genomics, core proteome and pan proteome can also be obtained within multiple strains under the same culture conditions. In this study we present the core proteome and pan proteome of four epidemic Salmonella Paratyphi A strains cultured under laboratory culture conditions. The proteomic information was obtained using a Two-dimensional gel electrophoresis (2-DE) technique. The expression profiles of these strains were conservative, similar to the monomorphic genome of S. Paratyphi A. Few strain-specific proteins were found in these strains. Interestingly, non-core proteins were found in similar categories as core proteins. However, significant fluctuations in the abundance of some core proteins were also observed, suggesting that there is elaborate regulation of core proteins in the different strains even when they are cultured in the same environment. Therefore, core proteome and pan proteome analysis of the multiple strains can demonstrate the core pathways of metabolism of the species under specific culture conditions, and further the specific responses and adaptations of the strains to the growth environment.